Vestígios para uma crítica da cultura - Costa Murad, Larissa (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
In this article, we revisit the contributions of radical critique, primarily those of Anselm Jappe, with the aim of unveiling some contradictions of capitalism that seem to us to be determinant in the production of culture and subjectivity. Considering the fetishistic character of this social form exposed by Marx in the Grundrisse and the consequent negation of culture as a space of self-determined human creation, it is urgent to consider spaces for the construction of another sociability, where subjectivities are not shaped by abstract social bonds. In this sense, we will outline a critique of some categories considered by Marx fundamental in the constitution of this social form in its multiple determinations, such as: value, commodity, labor, and time. Based on these and the recovery of the contributions of authors from the Frankfurt School, a critique of culture is delineated and, consequently, of the place reserved for subjects and their practices in the process of consolidating capital as the predominant social form.